Problem wyrównywania szans edukacyjnych na łamach "Głosu Nauczycielskiego" = Problem of levelling educational chances in the columns of the "Głos Nauczycielski" magazine - Kukiełko, Kalina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this paper is to present the results of a text analysis conducted in relation to articles from the "Głos Nauczycielski" weekly magazine. The analysed articles are chosen from 350 issues of "Głos" (from September 1999 till September 2006) and refer to teachers` view on levelling educational opportunities (differences between poor and rich pupils as well as those from cities and villages) in the context of the reform of education. The most important problems include teachers` protests and strikes, pupils` marginalization due to their Barents` material status, the segregation of children at school, children`s poverty, etc.
Keywords: Ziemia Lubuska - czasopisma; czasopisma polskie; czasopisma lokalne; czasopismo naukowe